Communications for the America’s Cup Challenge - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2018)
Two historic papers from a special issue of the Journal in 1986 featuring the communication requirements for the America’s Cup 1986/87 challenge in Fremantle.